APPLICATION OF E-LEARNING ADAPT TECHNOLOGY IF TO OVERCOME LEARNING DESIGNS - Herman Dwi Surjono (Jurnal Penelitian Saintek, 2013)
This study aims to design and implement adaptive e-learning technology to address the diversity of student learning styles. This system is expected to overcome the problems of conventional e-learning that gives the same material to each user. This research uses the R D approach. The research procedure includes: (a) analysis, (b) design, (c) implementation, and (d) evaluation. Analysis of consistency and accuracy of the contents carried out on the data at the stage of analysis and design. Descriptive analysis is performed on all data that can be tabulated so that meaningful. The result of this research is adaptive e-learning model to the diversity of student learning style. In the development process is generated also documentation needs description, function description, main features, architecture, and use case diagrams. The e-learning model is implemented with LMS Moodle and the adaptive function is made in module form. Performance, the first system identifies the trend of learning styles through a questionnaire that is Visual, Auditory, or Kinesthetic. Furthermore scores are used by the system as the basis for giving different materials to the students.